Advantages of Molecular Weight Identification during Native MS Screening - Khan, Ahad; Bresnick, Anne; Cahill, Sean; Girvin, Mark; Almo, Steve; Quinn, Ronald (Planta Medica, 2018)
Native mass spectrometry detection of ligand-protein complexes allowed rapid detection of natural product binders of apo and calcium-bound S100A4 (a member of the metal binding protein S100 family), T cell/transmembrane, immunoglobulin (Ig), and mucin protein 3, and T cell immunoreceptor with Ig and ITIM (immunoreceptor tyrosine-based inhibitory motif) domains precursor protein from extracts and fractions. Based on molecular weight common hits were detected binding to all four proteins. Seven common hits were identified as apigenin 6-C-β-D-glucoside 8-C-α-L-arabinoside, sweroside, 4′,5-dihydroxy-7-methoxyflavanone-6-C-rutinoside, loganin acid, 6-C-glucosylnaringenin, biochanin A 7-O-rutinoside and quercetin 3-O-rutinoside. Mass guided isolation and NMR identification of hits confirmed the mass accuracy of the ligand in the ligand-protein MS complexes. Thus, molecular weight ID from ligand-protein complexes by electrospray ionization Fourier transform mass spectrometry allowed rapid dereplication. Native mass spectrometry using electrospray ionization Fourier transform mass spectrometry is a tool for dereplication and metabolomics analysis.
Keywords: dereplication; ligand-protein complex; metabolomics; molecular weight; native mass spectrometry